A1 Adenosine Receptor Signaling and Therapeutic Target in Diabetes - Ansari, HR (International Journal of Pharmaceutical & Biological Archive, 2011)
ABSTRACT Diabetes is one of the risk factors to human health which progressively leads to cardiovascular complications such as ischemic heart disease, renal nephropathy, hypertension, endothelial dysfunction, and atherosclerosis. The biochemical and morphological abnormalities in various animal models has been reported in the literatures. These changes may be attributed to altered action of adenosine receptors and these receptors are named as A1, A2A, A2B and A3, mediate their effector functions through a G-protein signalling. Among these A1AR, couples to adenylate cyclase through Gi-protein and leads to vasoconstriction and fatty acid metabolism. Endothelial dysfunction has been known to be one of the factors being responsible for pathogenesis of vascular disease in diabetes. This review will give a general overview of the adenosine receptor and focuses on the role of A1AR in diabetes. The insight into the signaling pathway through A1AR could be helpful in developing a novel therapeutic tool to regulate the pathophysiological conditions that arises progressively in diabetes.